Human Being – Organization Homomorphism: Between Autopoiesis and Allopoiesis - Tarride-Fernandez, M (Emerald Group Publishing Ltd., 2016)
Purpose – The purpose of this paper is to discuss the condition of human beings and organizations producing goods and/or services as autopoietic and allopoietic machines, with the aim of establishing a functional homomorphism between the productive system of an organization and the productive system of human beings, a matter that involves reflecting on what human beings do that is distinguished as allopoietic by an observer. Design/methodology/approach – Use is made of Ashby’s concept of functional homomorphism to establish similarities between human beings and organizations. The definitions of autopoietic and allopoietic machine of Maturana and Varela are used to distinguish similarities and differences between what organizations do and what human beings do. Findings – As a result of using the autopoietic/allopoietic viewpoint, it is proposed to homologate the human nervous system with the production system of an organization, defining the latter as a world-creating energy/communication processing system. Research limitations/implications – A homomorphism is established here between a human nervous system and the production system of an organization; it remains pending the other homomorphisms that can be made between the systems of the human body and the organization. Practical implications – A proposal is made to understand an organization as a world-creating energy/communication processing system, and it is estimated that this would imply displacing attention, at present strongly centered on the generated products and/or services, toward the sense that they have for both persons and society, restating the question on the world we construct/live in, from the organizational standpoint. Originality/value – Human beings are seen as allopoietic machines, aiming to contribute to the discussion about what it is that we call human, homologating it with the work of an organization. As a result a new definition of organization is proposed. © 2016, © Emerald Group Publishing Limited.